Disiplin Kerja Dalam Kinerja Guru Di Smp Negeri 14 Palu - Pratiwi, Wiwi; Nuraisyah; Amijaya, Meldi (JPS: Journal of Publicness Studies, 2025)
Work Discipline in Teacher Performance at SMP Negeri 14 Palu". Guided by Intam Nuraisyah, as (Supervisor I) and Meldi Amijaya as (Supervisor II). This study aims to find out how the work discipline and performance of teachers in SMP Negeri 14 Palu are. The basis of the research used in this study is a qualitative approach with a descriptive type. This research is classified as a descriptive qualitative research type because this research provides an overview of the research results by describing the actual data obtained in the field. This research will describe Work Discipline and Teacher Performance. Based on the results of the study, it was concluded that teachers' work discipline is an important factor that affects their performance in carrying out their duties as educators. Work discipline is understood as a form of responsibility, awareness, and commitment to regulations, time, and professional duties, which is reflected in punctuality of attendance, compliance with school rules, completion of teaching equipment, and involvement in school activities. High work discipline also has a positive impact on the quality of learning, relationships with students, and the trust given by school leaders. Despite obstacles such as high administrative burdens and limited support systems, teachers still strive to maintain discipline through personal awareness and strong organizational cultural support. Therefore, teachers' work discipline is not only influenced by internal factors, but also highly dependent on leadership, school management, and the efficiency of the work system that supports the creation of optimal teacher performance.